(untitled) (Scientific journal of the Fergana State University, 2023)
It is a natural process that various changes in the meanings of words occur during the development of the language. Some words used in the old Turkic language have undergone certain spiritual changes in the modern Uzbek language. The meaning of some words has narrowed, some have expanded, and some have been used in the opposite sense. In this article, the phenomena of expansion and contraction of word meanings during the development of the language were highlighted on the example of a number of lexemes used in the work "Devonu lugotit turk". Lexemes such as jigit, кэjiк, jïлқï, cïғïр, эрÿк, алқïш,aмaч, кӭсäк, эркӓк, кöl, қïшлағ, jаjлағ, оғлан were used in the old Turkish language. By the later stages of the development of the language, certain semantic changes took place in the composition of these lexemes. Such changes in the development of word meaning were explained on the basis of methods of classification, description, comparison and linguistic analysis. A number of dictionaries were used to explain the meanings of the words. Sh. Rakhmatullayev, M. Mirtojiev, H. Dadaboyev, N. Rahmonov, Q. Sodikov, B. Abdushukurov, Sh. Usmanova, Sh. Egamova, A. Mominova. The opinions expressed by scientists such as on the expansion and narrowing of the meaning of words were analyzed, the reaction was expressed, it was noted that this phenomenon was not a special object of research in Uzbek linguistics.